The Effect of Digital Technology on Criminal Law Enforcement: An Analysis of Cybercrime and Its Handling - Eka Setiyawan, Novan; Karauwan, Donny Eddy Sam; Jumiran; Ghafar, Abidah Abdul (Mawaddah: Jurnal Hukum Keluarga Islam, 2024)
This research aims to identify the impact of digital technology development on criminal law enforcement, especially in the context of cybercrime. The research uses a normative juridical method with a literature analysis approach (library research), which includes a review of laws and regulations, court decisions, and case studies related to cybercrime. The results show that digital technology has facilitated significant changes in the modus operandi of cybercrime, ranging from phishing to attacks using artificial intelligence (AI) and cryptocurrency, which complicates law enforcement. The contribution of this research is to offer strategies for improving legal responses to cybercrime, including strengthening international cooperation, enhancing the technological capacity of law enforcement, and updating regulations. The novelty of this research lies in emphasising the importance of technological adaptation in law enforcement, especially in the face of the increasingly complex and global modus operandi of cybercrime.